Faktor Risk Profile, Struktur Good Corporate Governance dan Capital Merupakan Indikator untuk Mengukur Kinerja Keuangan Bank : (Studi Kasus pada Bank Konvensional yang Terdaftar di Otoritas Jasa Keuangan Periode 2020-2024) - Wahyudin Wahyudin; Grace Christien Sumakul (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study is secondary data sourced from the publication of financial reports and annual reports on the website www.ojk.go.id. Hypothesis results Based on the phenomenon of ROA, NPL, LDR graphs showing fluctuating NPL and CAR results in the 2020-2024 period still show fluctuating results in the 2020-2024 period. The lack of openness, ineffective supervision carried out by the Institution on managers will result in financial manipulation by managers which will later affect the decline in the company's financial performance. Insufficient DKI supervision causes GCG not to run optimally. Weak DD performance is indicated by the absence of openness principles between DD and shareholders. The existence of fraudulent practices, one of which arises from the performance of the KA which is dishonest or not independent.